Doping ve sportu - Jeschke, J; Nekola, J; Chlumský, J (Casopis lekaru ceskych, 1999)
The first organized doping controls were carried out in the 1970s. In 1993, the Czech Antidoping Charter was signed and the Antidoping Committee was established. The medical commission of International Olympic Committee decides, which substances and methods are prohibited. The current classification is as follows: I. prohibited classes of substances--stimulants, narcotics, anabolic agents, diuretics and some hormones. II. prohibited methods--blood doping and pharmaceutical, chemical or physical manipulation. III. classes of drugs subject to certain restrictions--alcohol, marijuana, local anesthetics, corticosteroids and beta blockers. All substances are characterized from the ergogenic viewpoint and health risks are particularly emphasized. In practice, doping control starts by drawing the athletes and ends by urine sample analysis in a special laboratory. In case of positive results, the sportsman is banned from sports activity for 3 months, 2 years or for the rest of his life. In 24 worldwide laboratories in 1995 93,938 urine samples were analyzed. 1516 (1.61%) proved to be positive, including 986 anabolic steroid use. In 1997, the Czech laboratory carried out 843 checks, of which 15 (1.7%) were positive. The largest positive doping group were body builders. Doping poses a major risk among junior sportsmen. Prevalence worldwide is estimated at 2-10% of the male population. In the future a severe antidoping attitude, as well as antidoping enlightenment, are certain to continue. By these standards the activity of the Czech Antidoping Committee is on a very high level.
Keywords: Česká republika; lidé; mužské pohlaví; Substance Abuse Detection; odhalování abúzu drog; Doping in Sports; doping ve sportu; Male; Czech Republic; Humans